Knowledge Mobilization as a Tool of Institutional Governance: Exploring Academics’ Perceptions of “Going Public” - Cain, Kate; Shore, Krystle; Weston, Crystal; Sanders, Carrie B (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2018)
In Canada there are growing discussions concerning the role of publicly funded universities and the impact of academic research. The integration of neoliberal practices and market rationalities place pressure on universities to “go public” in order to demonstrate relevance and accountability. Researchers are encouraged or even required to engage the public through knowledge mobilization activities. Our study provides an empirical analysis of knowledge mobilization in order to understand its perceived impact on public criminology, and more broadly the production and dissemination of criminological research. We argue that the institutional shift toward knowledge mobilization is perceived as a tool of institutional governance to demonstrate organizational accountability that shapes the production and dissemination of criminological knowledge.In Canada there are growing discussions concerning the role of publicly funded universities and the impact of academic research. The integration of neoliberal practices and market rationalities place pressure on universities to “go public” in order to demonstrate relevance and accountability. Researchers are encouraged or even required to engage the public through knowledge mobilization activities. Our study provides an empirical analysis of knowledge mobilization in order to understand its perceived impact on public criminology, and more broadly the production and dissemination of criminological research. We argue that the institutional shift toward knowledge mobilization is perceived as a tool of institutional governance to demonstrate organizational accountability that shapes the production and dissemination of criminological knowledge.